Classroom observations: How do teachers teach learning strategies? - Granström, Mikk; Kikas, Eve; Eisenschmidt, Eve (Frontiers in Education, 2023)
The aim of this study was to find out which learning strategies teachers teach, either directly or indirectly, and how classroom observations are related to teachers’ knowledge of learning strategies. Seven different learning strategies were used. The Learning Strategy Teaching Observation Instrument (LSTOI) was developed for this study. Forty-five video-based classroom observations were conducted. Teachers showed strong knowledge of learning strategies, but they did not directly teach about strategies in the classroom. In order to find out how teachers support learning strategies in the classroom, we conducted a detailed analysis of two teachers who provided the greatest amount of direct strategy instruction. Results showed that, although these teachers gave more direct strategy instruction than others, they justified the usefulness of strategies by saying that students will achieve better results in an upcoming test or examination. A better approach would be to explain the long-term impact of learning strategies and develop students’ skills in independently applying strategies in the future.